Heavy metal contamination and antibiotic residues in poultry feed and meat in Bangladesh (Asian-Australasian Journal of Food Safety and Security, 2021)
Presence of harmful contaminants and residues in poultry feed and meat have serious public health consequence. This study was carried out to identify and quantify antibiotic residues, heavy metals and toxins in poultry feed and meat in the two selected poultry production belts of Bangladesh. A total of 94 broiler feed samples and 60 broiler meat samples were collected and tested by Thin Layer Chromatography (TLC), High Performance Liquid Chromatography (HPLC) and Enzyme-linked Immunosorbent Assay (ELISA) for identification and quantification of the parameters. Antibiotic residues were detected in 18.89% of the feed samples, whereas, there were no toxin (Aflatoxin) positive samples. Among the antibiotic positive samples, Oxytetracycline (OTC) was found predominant and detected in 12.22% cases. The mean concentrations of Cadmium (Cd), Lead (Pb), Chromium (Cr) were found as 0.04 mg/kg, 1.28 mg/kg and 2.55 mg/kg respectively in feed samples. In the case of meat samples, the mean concentration of OTC, Ciprofloxacin (CIP), and Tetracycline (TCL) residues were found 8.67 ppb, 7.18 ppb and 0.81 ppb accordingly. The highest mean concentration of Oxytetracycline (OTC) (10.15 ppb) was found in samples collected from local poultry sellers, whereas, the highest mean concentration of Tetracycline (TCL) (1.35 ppb) and Ciprofloxacin (CIP) (10.62 ppb) were observed in the samples obtained from local farm. The highest percentage of TCL and CIP (64% and 48% respectively) were found in samples collected from local farm. Chlortetracycline (CTC) was found predominant (70%) in samples collected from Contract farms. On the other hand, out of 60 meat samples, Cd and Cr were detected in only one meat sample with concentration of 56.41 mg/kg and 14.44 mg/kg respectively. Lead was not detected in any of the meat samples.Asian Australas. J. Food Saf. Secur. 2021, 5 (2), 71-78